ChemInform Abstract: Tailoring the Catalytic Activity of Electrodes with Monolayer Amounts of Foreign Metals. Issue 34 (1st August 2013) - Calle‐Vallejo, Federico; Koper, Marc T. M.; Bandarenka, Aliaksandr S.
Abstract Review: 224 refs.